RETRACTED: Identification of Novel SCN5A Single Nucleotide Variants in Brugada Syndrome: A Territory-Wide Study From Hong Kong - Tse, Gary; Lee, Sharen; Liu, Tong; Yuen, Ho Chuen; Wong, Ian Chi Kei; Mak, Chloe; Mok, Ngai Shing; Wong, Wing Tak (Frontiers in Physiology, 2020)
Background: The aim of this study is to report on the genetic composition of Brugada syndrome (BrS) patients undergoing genetic testing in Hong Kong. Methods: Patients with suspected BrS who presented to the Hospital Authority of Hong Kong between 1997 and 2019, and underwent genetic testing, were analyzed retrospectively. Results: A total of 65 subjects were included (n=65, 88% male, median presenting age 42 [30-54] years old, 58% type 1 pattern). Twenty-two subjects (34%) showed abnormal genetic test results, identifying the following six novel, pathogenic or likely pathogenic mutations in SCN5A: c.674G>A, c.2024-11T>A, c.2042A>C, c.4279G>T, c.5689C>T, c.429del. Twenty subjects (31%) in the cohort suffered from spontaneous ventricular tachycardia/ventricular fibrillation (VT/VF) and 18 (28%) had incident VT/VF over a median follow-up of 83 [Q1-Q3: 52-112] months. Univariate Cox regression demonstrated that syncope (hazard ratio [HR]: 4.27 [0.95-19.30]; P=0.059), prior VT/VF (HR: 21.34 [5.74-79.31; P<0.0001) and T-wave axis (HR: 0.970 [0.944-0.998]; P=0.036) achieved P<0.10 for predicting incident VT/VF. After multivariate adjustment, only prior VT/VF remained a significant predictor (HR: 12.39 [2.97-51.67], P=0.001). Conclusion: This study identified novel mutations in SCN5A in a Chinese cohort of BrS patients.